ANALISIS PERAN PERBANKAN DALAM PENYALURAN KREDIT USAHA KECIL TERHADAP PENGEMBANGAN WILAYAH DI KOTA MEDAN - Ikwan Lubis; A M Hatuaon Sihite; Edizal Hatmi; Ilhamsyah Ilhamsyah (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2022)
The purpose of this study is to find out and analyze the effect of banking and labor loans on small business income and to find out and explain how the role of small businesses in regional development. As a source of data and information for banking policymakers in terms of providing small business loans, especially to support regional development in the city of Medan. The results of this study can be used to formulate wisdom programs and as a basis for making predictions of regional development in the city of Medan. The results of this study can be used as a tool to evaluate economic policies in the banking industry that have been implemented in the city of Medan. The regression equation can be obtained as follows: Y = 0.838 + 0.106 X1 + 0.261 X2, Where: Y = Total small business income per month X1 = Amount of banking capital / credit received X2 = Number of workers. Based on the equation above, it can be concluded, that the significant value between the amount of bank credit received and the total income per month (small business income) of 0.059 shows the result of the correlation of these two variables is significant which means that these two variables have a related relationship. The significant value between the number of workers and the total income per month of 0.000 shows that the correlation between these two variables is significant, which means that these two variables have a related relationship. In the appendix table, we can see that column R shows the correlation coefficient number, which is 0.702. This shows the relationship between the variables is very strong.